Amelioration of cognition by hesperidin-conjugated cobalt oxide nanoparticles - Anindita Behera; Bibhanwita Satpathy; Rajesh Kumar Sahoo; Pratap Kumar Sahu (Scientific Reports)
Abstract Diabetes mellitus is one of the metabolic syndromes that is associated with cognitive deficit, dementia, and Alzheimer’s disease (AD) like pathology due to impaired insulin-signalling in the brain, oxidative stress and mitochondrial dysfunction. Nanotechnology is one of the most promising techniques for targeting the brain. However, the toxicity of metal nanoparticles is one of the biggest challenges to be studied. In this study, cobalt oxide nanoparticles are conjugated to a bioflavonoid, hesperidin, a natural antioxidant. The study is designed to assess the efficacy and safety of the cobalt oxide conjugated hesperidin in the diabetes-induced cognitive deficit rat model. The neuropharmacological behaviour, in-vivo antioxidant status and level of acetylcholinesterase, nitrite, amyloid β, and pro-inflammatory cytokines were determined for cobalt oxide conjugated hesperidin and compared with bare cobalt oxide nanoparticles and hesperidin. The cobalt oxide conjugated hesperidin significantly improved learning and memory in the streptozotocin rat model. However, further studies are required to establish a cellular and molecular mechanism involved in the neuroprotective activity of cobalt oxide-conjugated hesperidin.